Computational methods of signal recovery and recognition - Mammone, Richard J. (Wiley series in telecommunications., 1992)
A self-contained introduction to the field of computational methods of signal processing. Divided into four sections: an overview of vector-space techniques and how they apply to signal processing followed by signal recovery, adaptive signal processing and signal recognition. Includes computer codes for developing class projects in which students can examine the behavior of algorithms and devise their own applications project. A wealth of examples plus a diskette are also provided.